Efektivitas Penyampaian Informasi Dan Pengetahuan COVID-19 di Universitas Malikussaleh - Teuku Ilhami Surya Akbar; Sarah Rahmayani Siregar; Muhammad Sayuti; Cut Miftahul Jannah (Majalah Kedokteran Indonesia, 2021)
Introduction: A communicative approach that is educative in nature is a strategy carried out by the Unimal Covid 19 task force in carrying out its duties. The communication media used so far are the use of unimal official social media accounts, websites, Instagram, Facebook, as well as dissemination of information through the assistant deans of student affairs in each study program to ensure the information to be conveyed can be conveyed. Method: The sampling technique used purposive sampling technique. This type of research is a descriptive study with a cross sectional survey design. The samples in this study were all active lecturers and students who filled out questionnaires through the Google Form application in July - December 2020. Result: The sample in this study amounted to 434 samples (58 lecturers and 376 students). The results showed that the information on COVID-19 was received quite effectively. This is indicated by the percentage of respondents' answers that 80,8% have received COVID-19 information and for the respondents' knowledge is good, which is shown by the percentage of respondents' answers, namely 87.5% who understand how to prevent and spread COVID-19. Conclusion: The percentage of receiving information and knowledge about COVID-19 by lecturers and students of Unimal is effective and good, this is indicated by 80,8% and 87.5% of respondents have received information and understand how to prevent COVID-19 at Unimal. This success is inseparable from the communication media used by the COVID-19 Task Force. Communication media is the main point that attracts the attention of every individual, especially in the process of disseminating information.